Querelles des fantastiqueurs : le problème des motifs fantastiques polyvalents et de leurs anastomoses à l’exemple de Lokis de Prosper Mérimée - Gadomska, Katarzyna (Romanica Silesiana)
The present paper discusses the theme of quarrels between critics of fantastique literature. It focuses on quarrels concerning the lists of supernatural topics as well as one about the interpretation of the topic of Lokis of Prosper Mérimée. Key words: Fantastique, quarrel, supernatural, list, topic, vampirism, lycantropy.